Utilization of Senduduk Fruit Extract (Melastoma malabathricum) for Natural Color in Lip Cream - Zulaicha, Annisaa Siti; Munawaroh, Khoryfatul; Saputra, Iwan Syahjoko; Setiajaya, Arif (Walisongo Journal of Chemistry, 2023)
Decorative cosmetics function to beautify your appearance with a combination of colors such as blush, hair dye and lip color . A class of cosmetics that women always use to give a more attractive appearance are decorative cosmetics such as lips cream. The coloring ingredients added to lip cream preparations are chosen from an economic perspective, but the optimal level of color stability means that many manufacturers still use dangerous chemical dyes such as Rhodamine B in their products. This dye can cause irritation to the respiratory tract and is carcinogenic. Therefore, the aim of the research is to formulate a lip cream preparation with natural coloring agent from sendunia fruit extract that is safe, useful and of good quality through physical and stability tests. Extraction was carried out using the maceration method for 3x24 hours using 96% ethanol solvent. Senduduk fruit extract lip cream is formulated into 4. The base comparisons carried out were (carnauba wax: microcrystaline wax) F 0 (12.6; 10.6), F1 (9.6; 7.6), F2 (7.6; 9.6), and F4 (9 ;9), physical properties assessed from the organoleptic test, homogeneity test, spreadability test, adhesion, pH test. The results of the hedonic test can be concluded that F2 color is the best formulation interested.